OMSCS: The Revolution Will Be Digitized: Lessons learned from the first five years of Georgia Tech's Online Master of Science in Computer Science program. - Galil, Zvi (Communications of the ACM, 2020)
The article outlines the Online Master of Science in Computer Science program from Georgia Tech.